JUDICIAL SUPERVISION OF THE ENFORCEMENT OF COURT DECISIONS - Shvachka, Victoriia; Lukyanchykova, Alona; Sirenko, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to highlight issues of judicial control over the enforcement of court decisions and to define judicial control as one of the effective means of influencing the enforcement of court decisions. Positive developments in this area are evident, as reflected in the Commercial Procedure Code of Ukraine. Research methods: methods of analysis and synthesis were used to study scientific sources and judicial practice, comparative legal, systemic-structural, and logical-legal methods were used to analyze normative-legal acts, and a formal-logical method was used to form our own conclusions and proposals. Results: the effectiveness of the judicial system is determined not only by the speed and legality of dispute resolution, but also by the level of actual enforcement of court decisions. Courts play not only the role of arbitrator in a conflict, but also act as a guarantor of the restoration of the legitimate rights and interests of persons who have sought protection of their violated rights. Full restoration of violated rights is possible not only through the adoption of a lawful decision, but also through its proper and effective enforcement. In this regard, the issue of monitoring the enforcement of court decisions deserves special attention. The Constitution of Ukraine explicitly states that court decisions are binding throughout the territory of the state and grants courts the power not only to administer justice but also to monitor the enforcement of their decisions. Discussion: judicial control, like other elements of procedural control, should perform a balancing function - ensuring the rights of both parties: the plaintiff and the defendant. At the same time, it should be prompt and effective. The introduction of judicial control over the enforcement of court decisions requires a comprehensive approach to resolving a number of regulatory, organizational, functional, and procedural issues.